Passivity-based active stabilization for DC microgrid applications - Yu, Jiaqi; Yu, Jingrong; Wang, Yue; Cao, Yijia; Lu, Xiaonan; Zhao, Dongbo (CSEE Journal of Power and Energy Systems, 2018)
In this paper, an improved active stabilization strategy of the interface converters in microgrid applications is proposed on the basis of the passivity-based stability criterion (PBSC). As a critical part of AC and DC hybrid microgrids, the DC microgrid is taken as an example. In particular, a stabilization method with a proportional-integral (PI) controller and firstorder high-pass filter (HPF) is proposed to meet the passivity requirements of the overall control diagram with respect to the output voltage. Meanwhile, an output current feedback control loop is introduced to ensure the output impedance passivity. Moreover, a small-signal model of the parallel interface converter system is established to comprehensively study the influence of control parameters on the passivity of the converters. Based on the active stabilization method proposed in this study, by manipulating the control diagram of each interface converter, the passivity and stability of the DC microgrids with variable configuration can be guaranteed. Therefore, a generic and simplified design approach is realized. A simulation model with three interface converters is implemented in MATLAB/Simulink, and the effectiveness of the proposed passivity-based active stabilization algorithm is verified by using this simulation model.